Development Development of an Arduino Uno-Based Tactile Audio Electrical Circuit KIT To Train Visually Impaired Students' Mathematical Ability in Ohm's Law Experiment - Amran, Tria Ningsih S.; Otji, Sadriyansah ST; Ratnaningtyas, Delthawati Isti; Saehana, Sahrul; Haeruddin, Haeruddin; Zaky, Muhammad (Universitas Negeri Yogyakarta, 2025)
This study aims to develop an Arduino Uno-based Tactual Audio Electrical Circuit KIT tool and test its implementation in training the mathematical thinking skills of visually impaired students on Ohm's Law material. The problem identified is the difficulty of visually impaired students in conducting experiments and mathematical calculations on Ohm's Law material. Therefore, it is necessary to develop a KIT Tool utilizing Arduino Uno to produce sound output in the form of a guide to assembling electrical circuits and electrical measurement results. This research uses the 4D model Research and Development (R&D) method with Define, Design, Develop, and Disseminate steps. This research produced a Tactual Audio Electrical Circuit KIT equipped with audio counting aids to facilitate filling out Student Worksheets (LKS) on Ohm's Law experiments. Expert validation and empirical trials were conducted to ensure the feasibility of KIT in learning. The Arduino Uno-based Tactual Audio Electrical Circuit KIT is effective in helping visually impaired students understand the concept of Ohm's Law and train their mathematical thinking skills. This research contributes to the development of technology-based inclusive learning media and can be an inspiration for teachers in improving the quality of education for visually impaired students. It can be concluded that the tactual audio electrical circuit KIT produced received a positive response from the teacher with an average score of 4.22 with the standard